Mobile applications for hospitalized elderly people with frailty: Scoping review protocol (Research, Society and Development, 2024)
Objectives: To map the evidence found in the scientific literature on mobile applications used and developed to care for frail elderly people in hospital settings. Method: A scoping review (Scoping Study or Scoping Review) following the guidelines of the Joanna Briggs Institute to answer the research question: Which mobile applications have been used and developed to care for frail elderly people in hospital settings? The sources of information will be the databases, electronic library: LILACS, MEDLINE / via Pubmed, CINAHL and Scopus, EmCare, EMBASE, Web of Science, BDENF, SciELO, IEEE Xplore and, for the gray literature used the Catalog of Theses and Dissertations of the Coordination for the Improvement of Higher Education Personnel (CAPES) and Europe OpenGrey. Expected results: To present the findings in the various literature on mobile applications used and developed in the care of frail and hospitalized elderly people, detailing their respective information and evidence. Conclusion: This scoping protocol will constitute a preliminary exercise that will initiate the development of a study, as well as providing publicity and transparency in the scientific community.